Helideck Assessment for Ship Using Liquid Hydrogen as Fuel - Olav R. Hansen; Eirik S. Hansen; Steven Bosscher (Chemical Engineering Transactions)
CAP 437 has for decades been the most recognized standard to ensure safe operations at helidecks on offshore installations and ships. CAP 437 defines alert and no-fly criteria for helicopter operations related to environmental effects like structure-induced turbulence, thermal effects from flares, diesel and gas turbine exhausts, and unburnt hydrocarbon gas emission from cold flaring or emergency blowdown systems. For ships using liquid hydrogen (LH2) as fuel, similar assessments are highly relevant. To support the approval process of a superyacht with a 3 MW hydrogen fuel cell power plant and LH2 storage tank installed, a CAP 437 assessment was performed. In addition to a standard directional wind turbulence study above the helideck, both ignited and unignited releases of cryogenic and ambient temperature hydrogen due to possible failures or emergencies were assessed using CFD modelling. Plumes from fuel cell space ventilation exhausts were also studied. Due to the very different properties of hydrogen compared to hydrocarbon fuels it was necessary to modify the CAP 437 criteria to reflect the properties of hydrogen related to both the buoyant (thermal) plume criteria and unignited plumes of hydrogen potentially leading to helicopter engine surge. The main conclusion from the assessment is that while the standard turbulence criteria from CAP 437 should be followed, it is recommended to avoid/limit helicopter operations with winds from aft as a general precaution due to the helideck in the bow area. Hydrogen venting, while highly unlikely, could occur at any time, and represents a major risk for helicopter operations if the vent plume would ignite. In addition to defining a safe operating envelope for helideck operations under normal conditions, simulations were performed to understand selected emergency scenarios, including worst-case hydrogen venting scenarios with/without ignition of plume, and situations with lack of manoeuvrability so that wind direction relative to ship may not be controlled. Recommendations for a safest possible approach for such emergency situations are provided.